INFLUENCE OF VERTICAL CURVE ON HIGHWAY TRAFFIC SAFETY - D. D. Selyukov; N. V. Vishnyakov (Наука и техника)
The paper is devoted to a challenging problem of ensuring traffic safety on the sections of a highway vertical curve and it provides an analysis for works concerning design, lay-out and organization of a project roadway. A change in vehicle speed has been analyzed depending on the length of a curve and a maximum longitudinal slope of a project roadway. The paper presents statistical data about accidents in the Republic of Belarus for several years on the sections of curves pertaining to project roadways. Comparative analysis of difference between point marks on a parabola is given in the paper and the parabola is inscribed in the fracture of the project roadway while using two methods. The paper presents the following errors: geodetic measurements in excesses while laying out pavement, elevation points along pavement axis while making road pavement. Emergence of centrifugal force causes a change in shearing and holding forces. Excess of the shearing force on the holding one leads to spontaneous sliding in the direction of a shearing force vector. Technical solutions have been developped on the basis of systematic functional and active deterministic method. The solutions are protected by invention patents of the Republic of Belarus and they ensure safety passages of highway sections with this type of curves in a longitudinal profile. While constructing and accepting a road for operation it is necessary to control references of curve elements in the longitudinal profile according to the results of executive surveys and in case of operation it is necessary to inform a driver about a safety speed for a passage through such sections